Mobilization of intensive care unit patients during renal replacement therapy: a survey with physical therapists - Luciene di Santi Martins; Thamires Aparecida Carvalho de Matos; Leda Tomiko Yamada da Silveira (Fisioterapia e Pesquisa)
ABSTRACT Although physical therapy techniques are widely applied at the intensive care unit (ICU), patients under renal replacement therapy (RRT) are often excluded from mobility studies. We aimed to investigate which are the mobilization interventions performed by physical therapists in ICU patients during RRT and what is the perception regarding its safety. This was a survey study with physical therapists who work at ICUs that have continuous renal replacement therapy (CRRT) and/or intermittent hemodialysis (IHD) in the city of São Paulo, Brazil. A structured questionnaire was sent electronically. Responses were analyzed separately for CRRT and IHD and compared with proportion test. A total of 71 forms were received, and 51 were included. Physical therapists were employed at public (56.8%) and private hospitals, of secondary (54.9%) and tertiary levels. Nine physical therapists reported specific protocols for mobilization practice during RRT at the ICU. Mobilization interventions were performed more frequently during CRRT than IHD (91% vs. 65%, p=0.005). Passive and active limb mobilization were the most frequently performed interventions. 21% of respondents reported complications for IHD and 26% for CRRT, mainly related to the hemodialysis system. Many participants (66.7% for IHD and 44.1% for CRRT) reported to have never searched for literature recommendations. Among those who searched, the findings varied greatly. We concluded that there is lack of standardization for mobilization interventions during RRT. Mobilization is more frequently performed during CRRT and the most applied techniques are passive and active limb mobilization. Complications reported during the mobilization practice were mainly related to the hemodialysis system and not frequent.